Studi per l'insegnamento delle lingue europee Atti della prima e seconda giornata di studio (Firenze, 2002-2003) - Staton, Scott; Nicolás Martínez, María Carlota (Proceedings e report, 2005)
On 12, 13 and 14 May 2003 the second edition of the study days on didactic materials for the teaching of foreign languages was held in Florence. Numerous language teachers, mainly active in Italian universities but also in private and public high schools took part in these study days. The speakers addressed a wide range of issues ranging from the implications of the enlargement of the European Union to the educational use of new technologies, from aspects of contrastive linguistics to the use of foreign languages for the teaching of non-linguistic subjects. From this dialogue between different experiences and cultures, an extremely dynamic picture emerged, open to new methodological and scientific stimuli. The volume is the significant collection of over 40 interventions and represents a contribution to the discussion on the teaching of foreign languages.